6x+3=9x-5

Simple and best practice solution for 6x+3=9x-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+3=9x-5 equation:


Simplifying
6x + 3 = 9x + -5

Reorder the terms:
3 + 6x = 9x + -5

Reorder the terms:
3 + 6x = -5 + 9x

Solving
3 + 6x = -5 + 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
3 + 6x + -9x = -5 + 9x + -9x

Combine like terms: 6x + -9x = -3x
3 + -3x = -5 + 9x + -9x

Combine like terms: 9x + -9x = 0
3 + -3x = -5 + 0
3 + -3x = -5

Add '-3' to each side of the equation.
3 + -3 + -3x = -5 + -3

Combine like terms: 3 + -3 = 0
0 + -3x = -5 + -3
-3x = -5 + -3

Combine like terms: -5 + -3 = -8
-3x = -8

Divide each side by '-3'.
x = 2.666666667

Simplifying
x = 2.666666667

See similar equations:

| 3x-12=24-9x | | 11y-12y=12 | | [-18+(-3)]+4= | | 5=-3x+2-7x+203 | | 3(2x-8)-3=-7x+6(x+6) | | xx+10=875 | | X+10=2x+30 | | 8+7x=8x-2 | | g(x)=x^3-27 | | (-12+48i)+(15-21i)=o | | -4+[2+(-8)+(-1)]= | | -5=4.3-7.75 | | 4(1-6n)=-21+n | | -x-8=o | | 14+[-7+(-5)]= | | -4y+7=-9y | | -6x-13=1-8x | | 14+[-7+-5]= | | k^2+k-6=0 | | -2x-5y=-34 | | 2+5x=13+5x | | 2x+3y=26 | | 4+5=x+8 | | 594=-2(x-9)+3(7-8x)-17 | | 8-3xn=2 | | 2(3v+7)=-4(3-2v) | | x^2-.33x-7.7= | | G-12=-7 | | 2x+5n=11 | | 10a-35=8a+1 | | 4(9r+8)=-17+3r | | -4-3(1-7f)=22 |

Equations solver categories